A lab-on-a-chip for clinical analysis with acoustic microagitation based on piezoelectric poly (Vinylidene Fluoride) - Martins, P. (2008)
This paper reports on the incorporation and validation of a microagitation system based on a piezoelectric polymer, Poly(vinylidene fluoride) in its beta phase, β-PVDF, in a fullyintegrated disposable lab-on-a-chip for point-of-care testing and monitoring of biochemical parameters in biological fluids. The lab-on-a-chip concept offers a novel approach for clinical analyses, especially in biological fluids analyses, due to its portability, ensuring that the analysis can be performed at any location with quick results. Its microagitation system performance was successfully demonstrated by quantitative measurements of uric acid in human urine, thought other molecules or biological fluids can be also measured. The optimization tests prove that it is possible to use lower frequencies than resonance with no major changes in the mixing process. The effect of area and location within the lab-on-a-chip of the microagitation system was also considered.